2021
DOI: 10.3390/ph15010025
|View full text |Cite
|
Sign up to set email alerts
|

Differential Influence of Pueraria lobata Root Extract and Its Main Isoflavones on Ghrelin Levels in Alcohol-Treated Rats

Abstract: The study was carried out on alcohol-preferring male Wistar rats. The following drugs were repeatedly (28×) administered: acamprosate (500 mg/kg, p.o.), naltrexone (0.1 mg/kg, i.p), and Pueraria lobata (kudzu) root extract (KU) (500 mg/kg, p.o.) and its isoflavones: daidzin (40 mg/kg, p.o.) and puerarin (150 mg/kg, p.o.). Their effects on a voluntary alcohol intake were assessed. KU and alcohol were also given for 9 days in an experiment on alcohol tolerance development. Finally, total and active ghrelin level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 97 publications
(145 reference statements)
1
4
0
Order By: Relevance
“…In addition, puerarin has been shown to have anti-alcohol, liver-protecting and anti-inflammatory effects in previous studies. 2931 In our experiment, this results were confirmed that PUE-NP had better anti-alcohol, liver-protecting and anti-inflammatory effects on mice with alcoholic liver poisoning. The possible reason is that PLGA nanoparticles delayed the action time of drugs in the target organs, which indirectly enhances the pharmacological effect of Puerarin, Puerarin and PUE-NP also have certain protective effect on the kidney tissue damage.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In addition, puerarin has been shown to have anti-alcohol, liver-protecting and anti-inflammatory effects in previous studies. 2931 In our experiment, this results were confirmed that PUE-NP had better anti-alcohol, liver-protecting and anti-inflammatory effects on mice with alcoholic liver poisoning. The possible reason is that PLGA nanoparticles delayed the action time of drugs in the target organs, which indirectly enhances the pharmacological effect of Puerarin, Puerarin and PUE-NP also have certain protective effect on the kidney tissue damage.…”
Section: Discussionsupporting
confidence: 80%
“…These saponins have protective effect on liver tissue immune damage. Puerarin can protect liver injury through gastric absorption and induce apoptosis of activated hepatic stellate cells, 29,30 it could also reverse the chemically-induced liver fibrosis effectively. Studies have shown that when endotoxin from intestinal tract reaches the liver via portal vein, the reticuloendothelial system in liver (mainly Kupffer cells) can recognize and phagocytosis endotoxin through Toll-like receptor 4 (TLR-4) on the cell surface, which was digested and removed by lysosomes.…”
Section: Discussionmentioning
confidence: 99%
“…The control groups received rapeseed oil (OIL) alone in volumes analogous to the CBD. For the induction of alcohol tolerance, the model used in our previous experiments was applied, with slight modifications [ 4 , 62 , 63 ]. Briefly, 30% EtOH was administered intraperitoneally (i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, we focused on observing selected aspects of tolerance occurrence based on the assumption that changes in the tolerance development provided by some drugs may be valuable in explaining our observed alteration of the addiction process [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…It covers post-stroke depression as well as depression caused by coexisting conditions, such as diabetes, coronary heart disease, migraines, Parkinson’s disease, and others. KR has the potential for an alcohol intake reduction [ 39 ] and, thus, in the long-term, prevention of alcohol addiction [ 40 ]. Zhou et al gave alcoholic male Wistar rats puerarin, daidzein, and puerarin extract [ 41 ].…”
Section: Introductionmentioning
confidence: 99%